2018
DOI: 10.4066/biomedicalresearch.29-18-1074
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy students' knowledge and attitudes towards diabetes: a cross-sectional study

Abstract: Objective: This study aimed to evaluate knowledge and attitudes of pharmacy students about diabetes mellitus. Methods: A cross sectional study using self-administered questionnaire was conducted from 25 th February to 15 th March 2018 among pharmacy students of King Saud University. A total of 120 students were randomly recruited using a multistage sampling method and were invited to participate in the study. Results: A total of 43.1% (n=50) of the students had a good knowledge about diabetes mellitus. Majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“… 37 , 38 However, the current study results were better than an earlier study by Al-Aboudi et al who found 14.7% of the participants reported poor DM knowledge. 39 Meanwhile, the knowledge of DM is different with respect to different study populations, 40 , 41 for instance, a previous study by Wajid et al reported 43.1% of the diabetic knowledge, among pharmacy students, which is better than current study findings. Additionally, a recent study from western region of Saudi Arabia reported lack of knowledge and awareness of DM among Saudi population.…”
Section: Discussioncontrasting
confidence: 78%
“… 37 , 38 However, the current study results were better than an earlier study by Al-Aboudi et al who found 14.7% of the participants reported poor DM knowledge. 39 Meanwhile, the knowledge of DM is different with respect to different study populations, 40 , 41 for instance, a previous study by Wajid et al reported 43.1% of the diabetic knowledge, among pharmacy students, which is better than current study findings. Additionally, a recent study from western region of Saudi Arabia reported lack of knowledge and awareness of DM among Saudi population.…”
Section: Discussioncontrasting
confidence: 78%
“…Furthermore, even though a majority of faculty members had previously undergone training in both medical writing and research ethics, there was an overall positive ATP among them [ 10 ]. Furthermore, studies on healthcare students in many elements of healthcare behaviors and clinical knowledge-related assessments have been reported [ 21 , 22 , 23 , 24 , 25 ]. However, studies on plagiarism assessment among students were lacking or limited; therefore, this study would add beneficial knowledge in the research area and would serve as a future reference for upcoming studies.…”
Section: Discussionmentioning
confidence: 99%
“…There were previous studies that estimated knowledge, attitudes, and practice toward influenza and diabetes nationally ( 11 , 12 ), while international studies assessed the knowledge of thyroid cancer ( 13 ), and only a few studies evaluated the knowledge, practice, and prevalence of thyroid diseases in Saudi Arabia ( 1 , 5 , 6 , 14 , 15 ). Although the majority of earlier studies were carried out in other parts of Saudi Arabia, our study stands out for its original design and sample, complete attention to the thyroid, clinical information related to it, manifestations, symptoms, and other factors.…”
Section: Introductionmentioning
confidence: 99%